Antibacterial Retention of Star Anise (Illicium verum) Essential Oil and Oleoresin in the Cellulose-PEG Composite - Miranda, Fitri Ariadna Sodi; Elvina Dhiaul Iftitah; Warsito (Indonesian Green Technology Journal, 2023)
Star anise essential oil (EO) and oleoresin (OL) consists of various volatile compounds that can be easily damaged and affect their quality and function. The degradation is mainly caused by the deterioration and release of their active components. Encapsulating the extracts into a composite matrix can give slow release and minimize the contact between active compounds and surrounding. Cellulose-PEG composite has good compatibility and affinity, it can retain the extracts so does their biological activities. In this work, the essential oil and oleoresin were encapsulated into the cellulose-PEG composite with a ratio of 1:2 (µL EO and OL per mg of composite). The cellulose was obtained from extraction of star anise residue of EO and OL isolation. The extraction steps were pre-alkalization, alkalization, and three-stage bleaching. Antibacterial assay for the samples uses a combination of agar disc and well method, where the pure one uses the disc as absorbent and both the disc and composite are put in the well. The diameter of the inhibition zone against Staphylococcus aureus was observed once a week for eight week. The result shows that pure and composite-packed star anise essential oil and oleoresin samples have fluctuating antibacterial activity during the obeservation. Both packed EO and OL show a lower difference of the diameter of the inhibiton zone which indicated the composite can retain the antibacterial activity of the star anise essential oil and oleoresin. Keywords: Star anise, antibacterial, essential oil, oleoresin, composite.